Fluorescence acquisition during hybridization phase in quantitative real-time PCR improves specificity and signal-to-noise ratio. (December 2008) - Mehndiratta, Mohit; Palanichamy, Jayanth Kumar; Ramalingam, Pradeep; Pal, Arnab; Das, Prerna; Sinha, Subrata; Chattopadhyay, Parthaprasad
Quantitative real-time PCR (qPCR) is a standard method used for quantification of specific gene expression. This utilizes either dsDNA binding dyes or probe based chemistry. While dsDNA binding dyes have the advantage of low cost and flexibility, fluorescence due to primer dimers also interferes with the fluorescence of the specific product. Sometimes it is difficult, if not impossible, to standardize conditions and redesign primers in such a way that only specific fluorescence of the products of test and reference genes are acquired. Normally, the fluorescence acquisition in qPCR using dsDNA binding dyes is done during the melting phase of the PCR at a temperature between the melting points of primer dimers and the specific product. We have modified the protocol to acquire fluorescence during the hybridization phase. This significantly increased the signal-to-noise ratio and enabled the use of dsDNA binding dyes for mRNA quantification in situations where it was not possible when measurement was done in the melting phase. We have demonstrated it for three mRNAs, E6, E7, and DNMT1 with β-actin as the reference gene, and for two miRNAs. This modification broadens the scope ofqPCR using dsDNA binding dyes.